Combinational design of heterogeneous lattices with hybrid region stiffness tuning for additive manufacturing. (1st November 2021) - Yang, Nan; Song, Yifan; Huang, Jinlun; Chen, Yuetao; Maskery, Ian
Graphical abstract: Highlights: Combinational design is proposed to construct heterogeneous lattices with multiple substructures. Structures in hybrid regions between substructures can be automatically thickened and thinned. Effectiveness of hybrid region stiffness tuning method is numerically and experimentally investigated. Designed heterogeneous lattices can be fabricated by any suitable additive manufacturing technique. Abstract: Lattices with engineered properties are significant for engineering applications in the energy, aerospace, optics and medical sectors. Current additive manufacturing (AM) combined with computer-aided design (CAD) methods are not flexible enough to create multi-substructure lattices with locally varying geometrical features and mechanical properties. For example, if the struts of one substructure correspond spatially to the void of another substructure in the hybrid region, the resulting structure is disconnected there. When the number of substructures is large, such a problem becomes inevitable and intractable. Here we propose a new AM & CAD method integrating all the processes of designing a complex lattice structure, such as subspace partitioning, substructure rotation, filling in each subspace and connection, and hybrid region stiffness tuning. This method provides a general framework for designing heterogeneous lattice structures with disorder, gradient and hybrid features. Additionally, we numerically and experimentally investigate the effectiveness of our hybrid region stiffness tuning method. Using this new method, the problem of low volume fraction or disconnection in the hybrid region in multi-substructure lattices is overcome, and the resulting structures can be generated for analysis or fabrication by any suitable AM technique.